Socio-Economic Impact Assessment of Hydrogen Injection in the Natural Gas Network - Spyros Kyrimis; Petros Dimas; Dimitrios Stamopoulos; Aggelos Tsakanikas (Energies)
This study explores the feasibility parameters of a potential investment plan for injecting “green” hydrogen into the existing natural gas supply network in Greece. To this end, a preliminary profitability optimization analysis was conducted through key performance indicators such as the cost of hydrogen and the socio-environmental benefit of carbon savings, followed by break-even and sensitivity analyses. The identification of the major impact drivers of the assessment was based on the examination of a set of operational scenarios of varying hydrogen and natural gas flow rates. The results show that high natural gas capacities with a 5% hydrogen content by volume are the optimal case in terms of socio-economic viability, but the overall profitability is too sensitive to hydrogen pricing, rendering it unfeasible without additional motives, measures and pricing strategies. The results feed into the main challenge of implementing commercial “green” hydrogen infrastructures in the market in a sustainable and feasible manner.